World Bank's Climate Programs and Their Implementation in Selected African Countries - Dušková, Karolína; Hnát, Pavel, 1981-; Brellíková, Miriam; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2025)
The aim of this thesis is to critically analyze and describe the sustainable development programs offered by the World Bank Group, focusing on their specific implementation within selected African countries and sectors. The first part introduces the role of the World Bank in global climate governance, with a focus on its financing strategies, key challenges, and alignment with international frameworks such as the Paris Agreement and the SDGs. Through the use of climate indicators like the Environmental Performance Index and Green Growth Index, the thesis assesses each country’s climate resilience and highlights gaps in data, governance, and funding. The second part presents case studies that evaluate sector-specific climate interventions: climate-smart agriculture in Kenya, renewable energy in Ethiopia, and coastal and marine conservation in Mozambique. Findings reveal country-specific strengths, such as Kenya’s use of digital tools in agriculture and Ethiopia’s expansion of hydropower, alongside common barriers, including institutional limitations and low scalability. The thesis concludes that locally adapted, participatory approaches and stronger monitoring and evaluation systems are essential for making international climate finance effective and creating lasting outcomes.
Vedoucí práce: Pavel Hnát
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: mezinárodní obchod [obor bakal. práce]; bakalářské práce; bachelor's theses